Into the light - Beattie, Clint. 1981- (Mona Vale, N.S.W. : Ark House Press, 2011)
After 14 operations, 6 weeks of radiotherapy and 2.5 years of chemotherapy, Clint shares how God has worked through him and in him to heal and restore him to full health.
Keywords: Beattie, Clint, -- 1981-; Cancer -- Patients -- Biography; Healing -- Religious aspects